2018
DOI: 10.1177/1558944718771389
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cutaneous Warts With Multiple Puncture Technique

Abstract: Barbotage, the multiple puncture of cutaneous warts, may be a reasonable treatment with minimal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In 1969, Falknor et al 12 was the first one who started a new technique using only needles for pricking the warts as a modality of treatment. Also, Mclaughlin et al 13 used an 18‐gauge needle to puncture warts for the treatment of 16 patients. They reported that complete response was seen in 85% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, Falknor et al 12 was the first one who started a new technique using only needles for pricking the warts as a modality of treatment. Also, Mclaughlin et al 13 used an 18‐gauge needle to puncture warts for the treatment of 16 patients. They reported that complete response was seen in 85% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional needling creates a pathway for immune cells to access the lesion, and increases blood flow to the lesion, all of which may lead to an immune‐mediated destruction of the wart 30 . Like other forms of medicine therapy, intralesional drug therapy has significant downsides that have sparked discussion such as immediate side effects, including pain during administration, bleeding, high risk of infection, and allergic reaction in addition to skin changes such as atrophy, telangiectasia, and pigmentary changes 31…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional needling creates a pathway for immune cells to access the lesion, and increases blood flow to the lesion, all of which may lead to an immune-mediated destruction of the wart. 30 Like other forms of medicine therapy, intralesional drug therapy has significant downsides that have sparked discussion such as immediate side effects, including pain during administration, bleeding, high risk of infection, and allergic reaction in addition to skin changes such as atrophy, telangiectasia, and pigmentary changes. 31 The promising results of this study, encourage the use of combined intralesional furosemide and digoxin as a successful therapy in cases of multiple cutaneous warts with low/absent recurrence potential, insignificant adverse effects and the absence of scarring that may occur with other conventional destructive modalities.…”
Section: Discussionmentioning
confidence: 99%
“…These micro injuries set up a wound healing cascade, in which platelets release chemotactic and growth factors causing invasion of other platelets, neutrophils, monocytes/macrophages, and new collagen production (De Vita and Goldust, 2018). It also creates a pathway for immune cells to access the lesion, and increases blood flow to the lesion, all of which may lead to an immune-mediated destruction of the wart (Mclaughlin et al, 2019).…”
Section: -Fluorouracil (5-fu) Is An Antimetabolite That Suppresses Ce...mentioning
confidence: 99%